Impact of verbal feedback on repeat sprint performance - Clawson, B. P. (Oklahoma State University, 2021)
INTRODUCTION: Verbal feedback is often used in sports by coaches, trainers, etc. to improve an athlete`s ability to perform their given tasks. However, little research has been conducted to confirm that an athlete`s performance will improve a significant amount when verbal feedback is given. Therefore, this study was completed in order to determine how significant the relationship between verbal feedback and an athlete`s ability to accomplish a given task to the best of their ability was. METHODS: Participants individually completed two sessions of ten 20-meter sprints, one session where feedback was given and another where no feedback was given. 20-meter sprint times from both sessions were collected and averaged for 15 (10 males; 5 females) competitive club athletes belonging to 3 different teams in this study. These times were collect along with anthropometric information of the participants (age, height and weight). A descriptive statistical analysis and paired T-test of the recorded times was applied in order to determine the significance of the given feedback and the athlete`s ability to maintain or improve sprint time. RESULTS: Tables 1 and 2 represent the data found. Results of the descriptive statistical analysis showed that feedback given to the athletes did encourage a significant decrease in sprint times as opposed to the sprint times without feedback (w/ feedback= 3.545 ± .244 and w/o feedback= 3.623 ± .242). A paired T-test showed a significant difference as well (t=-2.489, p=.030). DISCUSSION: This data provides information that supports the claim that verbal feedback can in fact improve an athlete`s ability to perform a task. PRACTICAL APPLICATION: Coaches, trainers and/or other professionals working with athletes may find this information persuasive in encouraging them to incorporate verbal feedback in their coaching or training styles during practices and performances with the athletes they preside over.